An assessment of preservice teachers’ content knowledge for teaching algebra: Evidence from Ghana Central Region - Sam, Leticia Nana; Asiedu-Addo , Samuel Kwesi; Enu, Justice (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
Teachers’ content knowledge plays a pivotal role in the development of mathematical knowledge for teaching. This paper investigates pre-service teacher (PST) content knowledge for teaching Algebra. The study adopts a quantitative descriptive survey design. Seventy-nine (79) second-year pre-service teachers were selected as participants, from two Colleges of Education in the Central Region of Ghana. Content Knowledge Test in Algebra (CTA) and a questionnaire were used in generating data. Analysis of PST responses to the CTA showed that pre-service teachers’ content knowledge for handling algebraic concepts in mathematics was superficial. Among other things, the study also found methods of teaching, previous algebraic content knowledge of pre-service teachers, level of interest, pre-service teachers’ first-year performance in mathematics, and lack of practice as factors which hinder pre-service teachers’ content knowledge in algebra. We conclude that mathematics teachers at the high school level should pay attention to their students’ algebraic knowledge since algebra forms the basis of mathematics and it is at this level that a strong foundation is laid for higher education.